Is Scores Derived from the Most Internationally Applied Patient Safety Culture Assessment Tool Correct? - Javad Moghri; Ali Akbari Sari; Mehdi Yousefi; Hasan Zahmatkesh; Ranjbar Mohammad Ezzatabadi; Pejman Hamouzadeh; Satar Rezaei; Jamil Sadeghifar (Tehran University of Medical Sciences, 2013)
Background: Hospital Survey on Patient Safety Culture, known as HSOPS, is an internationally well known and widely used tool for measuring patient safety culture in hospitals. It includes 12 dimensions with positive and negative wording questions. The distribution of these questions in different dimensions is uneven and provides the risk of acquiescence bias. The aim of this study was to assess the questionnaire against this bias.Methods: Three hundred nurses were assigned into study and control groups randomly. Short form of HSOPS was distributed in the control group and totally reversed form of it was given to the study group. Percent positive scores and t-test were applied for data analysis. Statistical analyses were conducted using SPSS Version 16.Results: Finally a total of 272 nurses completed the questionnaire. All dimensions with positive wording items in both groups had higher scores compared with their negative worded format. The first dimension "organizational learning and continued improvement" which had the only statistically significant difference, got 16.2% less score in the study group comparing the other group. In addition six out of 18 differences in questions were statistically significant.Conclusion: The popular and widely used HSOPS is subject to acquiescence bias. The bias might lead to exaggerate the status of some patient safety culture composites. Balancing the number of positive and negative worded items in each composite could mitigate the mentioned bias and provide a more valid estimation of different elements of patient safety culture.